Stereotypes in the performance of young actors in the contemporary Iraqi theater (Al-Academy, 2024)
Stereotyping in acting performance has been a prominent phenomenon recently, especially in youth theater performances, which resulted in a defect in the nature of conveying the dramatic and expressive dimensions in the actor’s performance. Therefore, the researcher decided to delve into this study, which she divided into the following:The introduction included the research problem, which was represented by the following question: Did the (young) Iraqi actor go beyond the stereotypical performance or perpetuate it in the Iraqi theatrical performance? And what are the reasons? Then the importance and goal of the research, then defining the research terms procedurally, then establishing a theoretical foundation consisting of two sections. The first section is entitled (The stereotypical similarity between form and content), which deals with the structure of the form in the show and how to communicate the contents in the theatrical performance. The second section discusses the title (Youth theater between stereotypes and innovation) which deals with how The emergence of youth theater and the extent to which they benefit from the performance references of the pioneers.(Research procedures) I determined the research population and the purposive sample, which was represented by the performance of actors in two performances: a presentation of the play (Rehearsal in Hell) and a presentation of the play (The Café).After analyzing the sample models, a set of results emerged